Effectiveness of individualized lung recruitment strategies at birth: an experimental study in preterm lambs - Tingay, David G.; Grychtol, Bartłomiej (American journal of physiology. Lung cellular and molecular physiology, 2017)
Respiratory transition at birth involves rapidly clearing fetal lung liquid and preventing efflux back into the lung while aeration is established. We have developed a sustained inflation (SIOPT) individualized to volume response and a dynamic tidal positive end-expiratory pressure (PEEP) (open lung volume, OLV) strategy that both enhance this process. We aimed to compare the effect of each with a group managed with PEEP of 8 cmH2O and no recruitment maneuver (No-RM), on gas exchange, lung mechanics, spatiotemporal aeration, and lung injury in 127 ± 1 day preterm lambs. Forty-eight fetal-instrumented lambs exposed to antenatal steroids were ventilated for 60 min after application of the allocated strategy. Spatiotemporal aeration and lung mechanics were measured with electrical impedance tomography and forced-oscillation, respectively. At study completion, molecular and histological markers of lung injury were analyzed. Mean (SD) aeration at the end of the SIOPT and OLV groups was 32 (22) and 38 (15) ml/kg, compared with 17 (10) ml/kg (180 s) in the No-RM (P = 0.024, 1-way ANOVA). This translated into better oxygenation at 60 min (P = 0.047; 2-way ANOVA) resulting from better distal lung tissue aeration in SIOPT and OLV. There was no difference in lung injury. Neither SIOPT nor OLV achieved homogeneous aeration. Histological injury and mRNA biomarker upregulation were more likely in the regions with better initial aeration, suggesting volutrauma. Tidal ventilation or an SI achieves similar aeration if optimized, suggesting that preventing fluid efflux after lung liquid clearance is at least as important as fluid clearance during the initial inflation at birth.
Gesehen am 18.09.2018
First published November 23, 2016